Global Research Trends and Recent Advances in Medicinal Plant-Synthesized Nanoparticles for Cancer Treatment - Tomi Lois Adetunji; Chijioke Olisah; Marvellous Amarachi Acho; Funsho Oyetunde-Joshua; Stephen O. Amoo (Plants, 2024)
Worldwide, cancer ranks among the foremost contributors to mortality despite recent medical progress. Alternative approaches in controlling various forms of cancer are being highly explored by researchers. This study provides the global research trends in the utilization of medicinal plant-synthesized nanoparticles for cancer treatment over the span of 18 years using scientometric analysis. Recent research advances on medicinal plant-derived nanoparticles for cancer treatment and their possible mechanisms of action were described. Relevant articles published between 2005 and 2023 were retrieved from Scopus and Web of Science and analyzed using RStudio and VOSViewer. Scientometric indicators were employed to analyze the results. The initial search returned 5695 articles, with a publication growth rate of 3.71% annually. Countries from Asia contributed the most (61.37%) to the total number of publications. The therapeutic effects of nanoparticles derived from medicinal plants can be attributed to various mechanistic pathways, including induced apoptosis from reactive oxygen species generation, as well as mitochondrial and cell membrane disruption, amongst others. Although some reported studies demonstrated promising safety and efficacy against certain cancer cells in vivo and in vitro, the little to no clinical data on medicinal plant-synthesized nanoparticles hinder the ability to make informed decisions about their clinical potential in cancer treatment.